Inflammatory pathways in acne - Orozco, Beatriz; Velásquez, Margarita María; Meléndez, Esperanza; Pabón, Juan Guillermo; Motta, Adriana; Anaya, Liliana; Atuesta, Juan Jaime; Balcázar, Luis Fernando; Barona, María Isabel; Becerra, Margarita María; Busi, Florinda; Campo, Martha Helena; et al. (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2013)
Acne vulgaris is a multifactorial inflammatory disease that involves the pilosebaceous unit, affecting 80% of the teenager population. Various mechanisms have been proposed in its pathogenesis, including special mention possibly an immunological mechanism associated with bacterial overgrowth. In this article we review the latest developments related to its pathophysiology and immunology, its relationship with Propionibacterium acnes and the possible therapeutic implications.